Peranan perpustakaan pesantren dalam pendidikan - Iskandar Sulaiman (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2007)
Education in both modern and old-fashioned community covers three important and integrated aspects, they are technical aspect to prepare students to get better life; social aspects to prepare citizens to continue their life; moral and spiritual aspect to develop citizens behavior and educate their citizens. Normally, teaching process is limited on things what grown up have done. Students imitate to learn social knowledge, technical and religion in order to prepare their future life. Key Words: Educational library